Indigenous Peoples Rights under International Law - Charters, Claire (The New Zealand Yearbook of International Law, 2008)
The developments that have taken place in New Zealand in relation to Indigenous Peoples rights under International law are discussed. Details of different committees formed and laws enacted to ensure and protect the same are highlighted.
Keywords: Indigenous peoples–Civil rights; Indigenous peoples–Legal status; laws; etc.; International law; New Zealand

The Maori Party and the Media: Representations in Mainstream Print Leading to the 2005 Election - Sullivan, Ann (Pacific Journalism Review, 2008)
This article investigates the 2005 pre-election print media coverage of the Maori Party and its candidates. It shows that while the reporters and journalists generally represented the Maori Party in a fair and unbiased manner, at times their reporting was undermined by unbalanced or biased editing or subediting.
Keywords: Elections–Press coverage; Journalism–Political aspects; Mass media–Political aspects; New Zealand; Press and politics

Does the New Zealand Government owe Māori an apology? - Hook, G. R.; Raumati, L. P. (Mai Review, 2008)

Restoring the Nation: Removing the Constancy of Terror - Jackson, Moana (TRADITIONAL KNOWLEDGE CONFERENCE 2008 TE TATAU POUNAMU: THE GREENSTONE DOOR, 2008)

Rapaki wahine whakamaumahara: memories of the Rapaki Branch Māori Women's Welfare League - Plumridge, Elizabeth (Canterbury University Press, 2008)
"Documenting the early days of the Rapaki Maori Women's Welfare League, this recollection strives to authenticate the oral histories of the early members that created the opportunity for Maori and Pakeha women to meet and trade skills. As membership of the branch changes, fewer and fewer people can speak with authority on the league's evolution, but this history chronicles the available facts and anecdotes that demonstrate the development of this important union."–BOOK JACKET.
Keywords: history; mana wāhine; māori womens welfare league; social conditions; wāhine māori

Kia tū ko taikākā: Let the heartwood of Māori identity stand - An investigation into the appropriateness of the legal definition of ‘Māori’ for Māori - Coates, Natalie (University of Otago, 2008)
Keywords: blood quantum; identity; law

The Māori seats in Parliament - Joseph, Philip (New Zealand Business Roundtable, 2008)
The Māori seats in Parliament / Philip A. Joseph.-book

Authenticating Mäori Physicality: Translations of ‘Games’ and ‘Pastimes’ by Early Travellers and Missionaries to New Zealand - Hokowhitu, Brendan (The International Journal of the History of Sport, 2008)
This paper theorizes how knowledge of indigenous tribal epistemologies was made ‘knowable’ through Enlightenment rationalism in an early colonial context. Specifically, the paper determines how and what knowledge of Mäori tribal physical activities was interpreted and authenticated through early travellers' tales and missionaries’ accounts in New Zealand. The central thesis argues that what was established as authentic and truthful aligned with Enlightenment rationalism, while those Mäori physical practices incomprehensible to Western understandings were deemed inauthentic and, consequently, were obscured and/or discarded. Throughout, the article theorizes the translation of knowledge into meaningful Western discourses and how these translations came to be crystallized in the colonial imagination.
Keywords: colonisation; cultural practices

Teaching Diversity, Advancing Democracy: Challenges for Citizenship Education in Aotearoa New Zealand - Tawhai, Veronica M.H. (The International Journal of Diversity in Organizations, Communities, and Nations: Annual Review, 2008)
The presence of diverse needs, interests and perspectives in society is a key measure of a healthy representative democracy. Learning about diversity, and how society provides for diversity, is therefore a valuable characteristic of citizenship education (Arthur and Davison, 2000; Berding and Miedema, 1998; Feinberg, Fields and Roberts, 1997). This paper presents the findings of recent research about citizenship education in Aotearoa (New Zealand). In particular, it explores what presence the notion of diversity has in New Zealand’s citizenship education programme (social studies). In New Zealand, the provisions for diversity are under constant political debate. This includes the provisions for indigenous political representation, such as the Maori parliamentary seats. The research utilized critical discourse analysis and content analysis methods. A review of the social studies curriculum revealed a strong focus on identity, culture and heritage in New Zealand, but an absence of material about how diversity is provided for in society. This includes the socio-political provisions for diversity in New Zealand’s democratic arrangements, such as guaranteed indigenous representation. The implications of this absence are discussed in terms of citizens’ understandings of democracy, equality, and the preparation of citizens to discuss these issues further.
Keywords: citizenship; civics; diversity; education; equality

Civics and citizenship education in Aotearoa New Zealand : multidimensional challenges. - Tawhai, V. M. H. (Social Educator, 2008)
This paper presents the findings of research about civics and citizenship education in Aotearoa New Zealand. Aspects of New Zealand's electoral system, such as the Maori representation, have long been the focus of political debate. This paper identifies the civics and citizenship education provided to New Zealand citizens about this debate. In New Zealand, civics and citizenship education is taught through the social studies curriculum. A review of the teaching units for social studies showed a considerable focus in New Zealand on aspects of citizenship such as identity, but an absence of material for civic knowledge such as the make-up of the electoral system. This absence includes a lack of material on the Maori electoral representation. These challenges are considered in context of the multidimensional citizenship model arising from the international Citizenship Education Policy Study (CEPS).
Keywords: civics; curriculum; education; māori electorates; political parties; political power; political socialisation

The Treaty of Waitangi in Contemporary New Zealand Politics - O'Sullivan, Dominic (Australian Journal of Political Science, 2008)
This paper identifies three discourses that are prominent in contemporary Treaty of Waitangi policy debate, each with significantly different implications for Maori political status within the modern nation-state. At one extreme the Treaty's significance is exaggerated by overemphasis on partnership as an implicit Treaty principle. At another extreme the Treaty's significance is understated by an assimilationist position that denies the Treaty's relevance to Indigenous rights which, in turn, imposes serious constraint on the extent to which partnership can actually develop into comprehensive policy practice. An alternative position is one that sees the Treaty, which is supported in international law, as affirming a twofold conception of citizenship as the basis of both individual and collective Maori rights.
Keywords: māori rights; partnership; tiriti o waitangi/treaty of waitangi; treaty obligations

Needs, Rights and "One Law for All": Contemporary Debates in New Zealand Maori Politics - O'Sullivan, Dominic (Canadian Journal of Political Science / Revue canadienne de science politique, 2008)
This paper examines contemporary debates in Maori politics by responding to the argument of the former leader of the opposition National party, Don Brash, that Maori public policy is most properly based on "need" alone because indigenous status offers no "rights" beyond those of common national citizenship. The paper's alternative argument is that the politics of indigeneity and associated theories of self-determination provide a way of avoiding a general belief that addressing need is all that is required to include Maori fairly in the national polity. It is argued that Maori ought to enjoy rights of indigeneity as the basis of an inclusive, cohesive and fair society. /// Cette étude examine certains débats dans le domaine de la politique maorie en répondant aux propos de l'ancien chef du parti National, Don Brash, selon qui la politique publique maorie se baserait le plus aptement sur la notion du seul 'besoin', le statut de peuple indigène ne conférant aucun 'droit' au-delà de ceux qu'accorde la citoyennenté nationale régulière. Nous proposons par contre que la politique de l'indigénéité et les théories de l'auto-détermination qui y sont associées constituent un moyen de parer à une croyance généralisée qu'il suffirait de suppléer au besoin pour inclure avec justice les Maoris dans la politique nationale. Nous démontrerons que dans une société inclusive, cohésive et juste, les Maoris devraient jouir des droits accordés par l'indigénéité.
Keywords: māori rights; protest; racism; ōrewa speech

Terror in our midst?: searching for terror in Aotearoa New Zealand - Keenan, Danny (Huia Publishers, 2008)
" On 15 of October 2007, three hundred police officers dressed in full riot gear, including balaclavas and sunglasses, raided the township of Ruatoki which lies at the northern end of the Ureweras. At the same time as Ruatoki was being lockeddown, police raids were taking place in other parts of the country. By the end of the day, 17 people were reported as arrested; four from Wellington, six in Auckland, one in Palmerston North, one in Hamilton and five in the Bay of Plenty area. The 'global war on terror', launched in the US five years earlier, had finally arrived in New Zealand "–Publisher website., Contributors: Pou Temara, Moana Jackson, Sue Abel, Maria Bargh, Te Urikore Biddle, Luke Crawford, Rawinia Higgins, Richard Hill, Brendan Hokowhitu, Craig Innes, Tonga Karena, Danny Keenan, Ocean Rīpeka Mercier, Dominic O'Sullivan, Māmari Stephens and Alice Te Punga Somerville.
Keywords: civil Rights; police; prevention; terrorism

Concurrent Narratives of Maori and Integration in the 1950s and 60s - Harris, Aroha (Journal of New Zealand Studies, 2008)
Maori and government policies of integration in the 1950s and 60s by accessing two concurrent narratives are discussed. The two narratives are the narrative of the state embedded in a one-size-fits-all Maori policy, and the narratives of the Maori 'business of life'.
Keywords: crown policy; social conditions; urbanisation

The future of rongoa Maori: wellbeing and sustainability. - Ahuriri-Driscoll, A.; Baker, V.; Hepi, M.; Hudson, M.; Mika, C.; Tiakiwai, S. (2008)
Rongoa Maori is a holistic system of healing that has developed out of Maori cultural traditions. It has a long history of usage and credibility among Maori, and increased interest in its revival and sustainability has prompted calls for its formalisation within the New Zealand public health system. Objective and methods The objectives of the research project were to: - Examine the contribution of rongoa Maori to indigenous wellbeing, and - Identify issues for the ongoing sustainability of traditional Maori healing in New Zealand. The research process was lead by Maori researchers in collaboration with Maori healers and stakeholders. Two literature reviews were undertaken; one to provide understanding of international developments in traditional medicine, and a second to review national policy/literature related to rongoa Maori. Four focus groups and five workshops were held with groups in five communities to explore current rongoa practice and service delivery and drivers/barriers to its ongoing utilisation. The participant groups were healers and their associates, and health and local authority stakeholders.
Keywords: hauora; health; rongoa